2017
DOI: 10.1371/journal.pone.0186158
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment with GnRHa or ulipristal acetate prior to laparoscopic and laparotomic myomectomy: A systematic review and meta-analysis

Abstract: BackgroundMyomectomy has potential risks of complications. To reduce these risks, medical pre-treatment can be applied to reduce fibroid size and thereby potentially decrease intra-operative blood loss, the need for blood transfusion and emergency hysterectomy. The aim of this systematic review and meta-analysis is to study the effectiveness of medical pre-treatment with Gonadotropin-releasing hormone agonists (GnRHa) or ulipristal acetate prior to laparoscopic or laparotomic myomectomy on intra-operative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…However, up to now, this potential benefit for UPA has not been yet demonstrated in published studies. A recent systematic review and meta-analysis reported that UPA has not been sufficiently evaluated yet for surgical outcomes [38]. Similarly, there are only limited data on the comparison between preoperative SPRMs and other hormonal therapies in patients undergoing hysteroscopic or laparoscopic myomectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to now, this potential benefit for UPA has not been yet demonstrated in published studies. A recent systematic review and meta-analysis reported that UPA has not been sufficiently evaluated yet for surgical outcomes [38]. Similarly, there are only limited data on the comparison between preoperative SPRMs and other hormonal therapies in patients undergoing hysteroscopic or laparoscopic myomectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, GnRH-as have been routinely employed in this setting, as they have demonstrated to reduce abnormal uterine bleeding before surgery, increasing hemoglobin levels, as well as to reduce size of fibroids and uterus. However, a not negligible issue is related to the fact that under the administration of these hormonal drugs, patients can experience a not negligible rate of menopausalrelated adverse events, which may limit adherence to the schedule [4].…”
Section: Commentary Preoperative Hormonal Treatment Before Laparoscopicmentioning
confidence: 99%
“…Overall, it should be under scored that until now few studies on surgical outcomes after UPA administration are available in the literature [7-9]; similarly, not sufficient data on the comparison between preoperative SPRMs and other hormonal therapies in patients undergoing laparoscopic myomectomy can be found [4]. Moreover, further trials should be planned for evaluating long-term outcomes such as frequency of myoma recurrence, recovery time and post-surgical quality of life after laparoscopic myomectomy with preoperative UPA use.…”
Section: Commentary Preoperative Hormonal Treatment Before Laparoscopicmentioning
confidence: 99%
“…GnRHas are associated with a greater decrease in fibroid and uterine volume compared to SPRMs. 9,29 When compared to no pretreatment, use of a GnRHa is associated with decreased fluid absorption at hysteroscopic myomectomy, 30,31 and decreased blood loss and transfusions at laparotomic/laparoscopic myomectomy 29,32 (Level I, A). The primary advantage of UPA over GnRHas is the rapid control of uterine bleeding (5-7 days with 10-and 5-mg UPA doses, respectively, vs 21 days for leuprolide, P < .01).…”
Section: The Pastmentioning
confidence: 99%